Utilizing evidence to drive program implementation: How Lot Quality Assurance Sampling (LQAS) surveys help districts to target underserved areas in Uganda - Kironde, Samson; Mabirizi, Joseph; Businge, Denis; Ssimbwa, Stephen; Orobaton, Nosa (USAID, 2006)
For e ective implementation of decentralized health systems at the local level, districts need to have accurate, up-to-date and representative information to guide decisions about where to focus resources in order to achieve maximum impact with the often limited resources at their disposal. However, many local government entities in Uganda have limited capacity and resources to measure outputs and outcomes in order to e ectively tailor interventions. Use of regular low cost Lot Quality Assurance Sampling (LQAS) surveys can help achieve this.